Energocentrum - vybrané části STP - Suchánek, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce Energocentrum - vybrané části STP řeší stavbu po stránce technologické z pohledu zhotovitele stavební zakázky. Zabývá se problematikou finančních, časových a přípravných požadavků, přičemž jako podklad sloužila diplomová práce studenta z ústavu Pozemního stavitelství.

Master thesis Energy centre - selected parts of building technology project is solving problems connected with technological issues from the construction work supplier point of view. This thesis concerns such a parts as financial, timing and preparations are. Material used as a base was a master thesis of the student from Civil engineering department.
Energy centre - selected parts of building technology project
Keywords: technologie; stavba; pasivní dům; sendvičové panely; zařízení staveniště; technologický předpis; harmonogram; rozpočet; technology; construction; passive house; sandwich panels; equipment of the construction site; technological standard; schedule of the work; budget